2007
DOI: 10.1111/j.1365-2923.2007.02769.x
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in multisource feedback: intended and unintended outcomes

Abstract: Findings suggest circumstances that may contribute to low consequential validity of MSF for doctors. Implications for practice include enhancing procedural credibility by ensuring reviewers' ability to observe respective behaviours, enhancing feedback usefulness by increasing its specificity, and considering the use of more objective measures of clinical competence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
163
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 128 publications
(169 citation statements)
references
References 19 publications
4
163
0
2
Order By: Relevance
“…If the students never summarized their quantitative data, StudentPEP results may have served like loose ends instead of being useful feedback. It has been found that facilitated reflection is helpful to assimilate and accept feedback given in multisource feedback sessions (Sargeant et al 2007). We have not done a qualitative analysis of the content or techniques used to foster reflection in such discussions.…”
Section: Reflective Discussionmentioning
confidence: 99%
“…If the students never summarized their quantitative data, StudentPEP results may have served like loose ends instead of being useful feedback. It has been found that facilitated reflection is helpful to assimilate and accept feedback given in multisource feedback sessions (Sargeant et al 2007). We have not done a qualitative analysis of the content or techniques used to foster reflection in such discussions.…”
Section: Reflective Discussionmentioning
confidence: 99%
“…18 However, doctors may not be inclined to use feedback for improvement, 25 with particularly few changes being made in response to positive feedback. 18 This study revealed difficulties in the interpretation of survey results because of the perceived low credibility and simplicity of numeric scores.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…18 However, doctors may not be inclined to use feedback for improvement, 25 with particularly few changes being made in response to positive feedback. 18 This study revealed difficulties in the interpretation of survey results because of the perceived low credibility and simplicity of numeric scores. Similar findings have Characteristics of effective feedback 17,[23][24] Practitioner views on patient experience surveys been reported in relation to the use of multisource feedback for physicians, where factors such as low credibility and the importance of opportunities for constructive reflection affect whether feedback has positive impacts.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…MSF is a reliable workplace-based assessment strategy 1 used to collect data on the performance of practicing physicians, and has been used extensively to assess physicians and guide continuing professional development in Canada, 2,3 the USA, 4,5 the UK 6,7 and Europe. 8,9 Generally in a MSF assessment, patients, co-workers (e.g., nurses, technicians, pharmacists), and medical colleagues provide data.…”
Section: Co-worker Familiarity and Physician Multisource Feedbackmentioning
confidence: 99%